PENGARUH KIAMBANG (SALVINIA MOLESTA) YANG DIFERMENTASI DENGAN RAGI TEMPE SEBAGAI SUPLEMEN PAKAN TERHADAP PENINGKATAN BIOMASSA AYAM PEDAGING - ZAMAN, QOMARUZ (LenteraBio: Berkala Ilmiah Biologi, 2013)
This study aimed to determine the dose of fermented kiambang as feed supplements for increasing biomass of broiler; to define the number of consumption of feed boiler; and to determine feed conversion number caused by kiambang consumption. This research was experimental research with Completely Randomized Design (CRD) using fermented kiambang concentration as experimental factor. Kiambang was given using 6 kinds of concentrations: 0%, 10%, 20%, 30%, 40%, and 50% for 4 times repetition at random design. The data including increase of biomass boiler, feed consumption data, and conversion feed data, tested using Analysis of Variant and continued by Duncan?s Multiple Range Test (DMRT) 5% if the first test result was significant. Based on the increase of biomass boiler, feed consumption, and feed conversion, the 50% fermented kiambang concentration showed the best result to increase boiler biomass. These results suggested that kiambang fermentation can increase broiler biomass, reduce the number of feed consumed, and feed conversion.